Television advertising's influence on parents' gift-giving perceptions. Issue 7 (12th November 2018) - Holiday, Steven; Norman, Mary S.; Cummins, R. Glenn; Hernandez, Terri N.; Holland, Derrick; Rasmussen, Eric E.
Abstract : Purpose: This study aims to examine factors, beyond child requests, that influence parents' perceptions of the most important gifts to give their children by assessing the influence of television advertising on children's programming. Design/methodology/approach: Using agenda-setting as a theoretical and methodological template, a content analysis of 7, 860 commercials in children's programming was compared using a questionnaire to 143 parents of 240 children to test the transfer of salience between advertising and parents' perceptions. The study also examined the role of child purchase requests in this relationship. Findings: The product categories that most prevalently advertised on children's television had a significant relationship with the product categories that parents perceived to be the most important to give their children as gifts. Furthermore, the results indicate that this relationship was not contingent upon parental advertising mediation or child product requests. Research limitations/implications: The results are limited to a single broadcast market during the Christmas season. Strategically, the research suggests that advertising through children's television programming may be an effective way to directly inform parents' gift-giving consideration sets, and this target and outlet should be strategically evaluated in subsequent campaign decisions about the marketing mix. Originality/value: The findings add new insights to the gift-giving literature, indicating that advertising in children's programming may be an alternative direct influence on parents' perceptions. This research also extends research on advertising agenda setting into the new context of commercial advertising of consumer products.